Preparation and In Vitro and In Vivo Performance of Magnesium Ion Substituted Biphasic Calcium Phosphate Spherical Microscaffolds as Human Adipose Tissue-Derived Mesenchymal Stem Cell Microcarriers. (4th June 2013) - Kim, Dong-Hyun; Kim, Tae-Wan; Lee, Ju Dong; Shin, Keun-Koo; Jung, Jin Sup; Hwang, Kyu-Hong; Lee, Jong Kook; Park, Hong-Chae; Yoon, Seog-Young
Abstract : Magnesium ion substituted biphasic calcium phosphate (Mg-BCP) bioceramic microscaffolds with spherical and porous morphology were successfully prepared using in situ coprecipitation and rotary spray drying atomization process for application of tissue engineering combined with human adipose tissue-derived mesenchymal stem cells (hAT-MSCs). After 4 weeks of immersion in Hanks' balanced salt solution (HBSS), Mg-BCP micro-scaffolds showed the enhanced biodegradation and bioactivity due to the substituted Mg 2+ ion present in the BCP structure. In this study, it was observed that hAT-MSCs have clearly attached on the surface of Mg-BCP micro-scaffolds. In addition, Mg-BCP micro-scaffolds exhibited the improved biocompatibility and osteoconductivity via in vitro and in vivo biological tests with hAT-MSCs. Therefore, these bioceramic micro-scaffolds had potential to be used as hAT-MSCs microcarriers for biomedical applications.